HARNESSING BIOMETRIC SIM REGISTRATION IN FIGHTING INSECURITY AND CRIMINALITY IN SOUTH- EASTERN NIGERIA - Shedrack Njoku, Chinwendu (African Journal of Social and Behavioural Sciences, 2026)
The rising incidence of insecurity and criminality in Nigeria, particularly in South- Eastern Nigeria, continues to threaten socio-economic stability, public safety, and national development. Criminal networks increasingly exploit mobile communication technologies to coordinate kidnappings, armed robbery, cybercrime, and other organized offenses, often relying on anonymity enabled by weak Subscriber Identity Module (SIM) registration systems. This study examines biometric SIM registration as a strategic intervention for combating insecurity and criminality in the region. Adopting a qualitative research design based on secondary data and theoretical interpretation, the study draws on criminological perspectives and biometric identification frameworks to assess the policy’s effectiveness. Anchored in structural functionalist theory, the analysis conceptualizes biometric SIM registration as a structural mechanism introduced to restore social order by linking mobile subscribers to verifiable biometric identifiers such as fingerprints and facial data. The findings suggest that biometric integration enhances traceability, strengthens intelligence-led policing, and aligns with primary and secondary crime prevention strategies by increasing the risk of detection and reducing opportunities for anonymous communication. However, challenges relating to data protection, institutional coordination, infrastructural deficits, and public trust limit its full potential. The study concludes that biometric SIM registration can significantly strengthen Nigeria’s security architecture if supported by robust governance mechanisms. It recommends that the National Identity Management Commission (NIMC) ensure the integrity and security of the National Identity Database (NIDB) to prevent breaches and fraudulent activities. Furthermore, the Nigerian Communications Commission (NCC), NIMC, and security agencies must establish a unified and real-time data-sharing protocol to enhance coordinated enforcement and investigative efficiency.